ROSOT KARBON TANAMAN PADA RUANG HIJAU DIKAMPUS UNPAD JATINANGOR, SUMEDANG JAWA BARAT - Deden Nurjaman; Teguh Husodo; Herry Y. Hadi Kusumah (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2017)
Carbon sink plants analysis from campus UNPAD Jatinangor green space a was conducted in January-March 2017. Campus UNPAD Jatinangor green space is divided into two parts namely cluster I (Campus Forest) and cluster II (Green Line of Road, Park, and Green Parking Area) green space. The purpose and objective of this research are to know the potential of biomass and carbon sink in the of cluster I and cluster II of UNPAD campus Jatinangor green space. The method used is the total census method. The result of the first cluster green space biomass density values obtained (DB) in the amount of 484.52 tonnes / Hectares, carbon density of 242.9 tonC / Hektares, and the value of the spare CO2 density (DCC) at 6780.31 tonCO2 / ha, with a total area of 62.59 hectares. DB value of RH cluster II in the amount of 505.90 tonnes / Hectares, density carbon (DC) amounted to 252.9 tonC / Hectares, and the value of 3077 tonCO2 DCC / Hectares, with a total area of 95.65 Hectares.DB value of cluster II green space in the amount of 505.90 tonnes / Hectares, density carbon (DC) amounted to 252.9 tonC / Hectares, and value of the spare CO2 density (DCC) of 3077 tonCO2 / Hectares, with a total area of 95.65 Hectares.There 4 kinds of plants obtained from Padjadjaran University campus Jatinangor green space which has the highest biomass and carbon sinks are Ficus Elastica (Roxb) with a value of 230345.06 kg of biomass and carbon sinks for 2708.71kg, ficus benjamina (L) with a value of 5314.68 kg of biomass, and the value sinks carbon at 2657.34 kg, Enterolobium cyclocarpum (Osbeck) with a value of 2677.49 kg of biomass and carbon sinks value of 1338.75 kg, Ficus virens (Aiton) with a value of 2148.77 kg of biomass and carbon sinks value of 1074.38 kg. Keywords:Carbon sink, Plant, Green Space, Campus UNPAD Jatinangor